The Importance of Product Reformulation Versus Consumer Choice in Improving Diet Quality. (11th May 2016) - Griffith, Rachel; O'Connell, Martin; Smith, Kate
Abstract : Improving diet quality has been a target of public health policy. Governments have encouraged consumers to make healthier food choices and firms to reformulate food products. Evaluation of such policies has focused on the impact on consumer behaviour; firm behaviour has been less well studied. We show that the recent decline in dietary salt intake in the UK was entirely attributable to product reformulation; consumer switching between products worked in the opposite direction and led to a slight increase in grocery salt intensity. These findings point to the important role that firms can play in achieving public policy goals.